2014
DOI: 10.1155/2014/496121
|View full text |Cite
|
Sign up to set email alerts
|

Median Preoptic Nucleus Mediates the Cardiovascular Recovery Induced by Hypertonic Saline in Hemorrhagic Shock

Abstract: Changes in plasma osmolarity, through central and peripheral osmoreceptors, activate the median preoptic nucleus (MnPO) that modulates autonomic and neuroendocrine adjustments. The present study sought to determine the participation of MnPO in the cardiovascular recovery induced by hypertonic saline infusion (HSI) in rats submitted to hemorrhagic shock. The recordings of mean arterial pressure (MAP) and renal vascular conductance (RVC) were carried out on male Wistar rats (250–300 g). Hemorrhagic shock was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Like in the previous study 17 , HSS infusion did not promote plasma volume expansion. Hence, volume replacement seems insufficient to explain cardiovascular hyperosmolarity-induced recovery.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Like in the previous study 17 , HSS infusion did not promote plasma volume expansion. Hence, volume replacement seems insufficient to explain cardiovascular hyperosmolarity-induced recovery.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, our data showed that the HSS infusion reestablished MAP and HR of sham rats. Several studies have reported HSS infusion-induced hemodynamic improvement after HH 9 , 17 . Highlighting the sympathetic component influence in the hyperosmolarity-responses, the sympathoinhibition generated in the renal territory during HH was maintained after sodium overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of intravenous hypertonic saline to restore arterial pressure in haemorrhaging animals is also blocked if the MnPO is inhibited by muscimol microinjection (Amaral et al . ). Pharmacological inhibition of AT 1 or NMDA receptors within the MnPO reduces the vasoconstrictor responses to cocaine or ice cold startle in a subgroup (vascular responders) of Sprague–Dawley rats, showing a role for the MnPO in stress‐mediated hemodynamic responses (Schwartz et al .…”
Section: Cardiovascular Regulationmentioning
confidence: 97%
“…Thus, the pressor response to hypertonic saline administered into the carotid artery or ICV can be blocked by injection of losartan, ouabain, b-endorphin or local anaesthetic into the MnPO (Yasuda et al 2000, Budzikowski & Leenen 2001, Stocker & Toney 2005, Caeiro & Vivas 2008, suggestive of an angiotensinergic AT 1 synapse within the MnPO influencing cardiovascular function. The effect of intravenous hypertonic saline to restore arterial pressure in haemorrhaging animals is also blocked if the MnPO is inhibited by muscimol microinjection (Amaral et al 2014). Pharmacological inhibition of AT 1 or NMDA receptors within the MnPO reduces the vasoconstrictor responses to cocaine or ice cold startle in a subgroup (vascular responders) of Sprague-Dawley rats, showing a role for the MnPO in stress-mediated hemodynamic responses (Schwartz et al 2008).…”
Section: Cardiovascular Regulationmentioning
confidence: 99%